Involvement of chemokine CXCL12 and its receptor CXCR4 in uterine receptivity and potential relationship to fertility in cattle: a mini review - D’Occhio, Michael J.; Campanile, Giuseppe; Baruselli, Pietro S. (Frontiers in Veterinary Science, 2025)
The establishment of a pregnancy in cattle relies on crosstalk between an embryo with high developmental competence and a responsive uterus. This often fails and the pregnancy rate in cattle is around 60–70% with natural mating and 50–60% for embryo transfer, with pregnancies typically higher in beef than high performing dairy. These pregnancy rates are primarily due to the loss of embryos in the 21-day window from fertilization to the initiation of attachment of the conceptus to the uterus. Considerable research has been devoted to defining high quality embryos; however, embryonic mortality remains a major cause of pregnancy failure. The latter highlights the critical importance of uterine receptivity in establishing a pregnancy. The uterus must be responsive to signals from the developing embryo to undergo a major structural and functional transformation to prepare for attachment of the conceptus and establishment of pregnancy. The chemokine CXCL12 and its receptor CXCR4 are expressed across somatic and neural tissues and are associated with tissue remodeling including angiogenesis. These are features of the change the uterus undergoes as it develops receptivity to the conceptus. The developing embryo produces CXCL12 and CXCR4 is present in uterine tissue, and a role for the CXCL12-CXCR4 axis have been demonstrated in early pregnancy. Chemokines including CXCL12 are likely to be important in embryonic survival and pregnancy in cattle.